UPAYA GURU AGAMA DALAM MENAGGULANGI KENAKALAN REMAJA (Studi Kasus di MA Balongrejo) - Nurul Indana (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
Adolescence is full of turmoil, they are filled with high curiosity that they do things that are not appropriate. The negative effects of globalization have made adolescents who abuse technology, such as watching television late at night with an interesting program that will have a negative impact on adolescents when the hours go up late so that teenagers will skip school because of late, smoking, rowdy in class cheating, fighting. This condition needs serious attention by the religion teacher at school, so that delinquency does not become a habit for the students. The results of this study indicate: There are several forms of efforts undertaken by Islamic religious education teachers in overcoming student delinquency, namely in collaboration with Religious Teachers, vice principals, vice of academic, classroom teachers, picket teachers, and student council and students with three phases, first preventive action, second repressive and third curative. There are several factors that support the efforts of religious teachers, including the existence of good cooperation that exists between parents of students and the school. The role of parents is very large for the achievement of the work done by religious teachers. While the inhibiting factors include the lack of student awareness to comply with school regulations and the lack of supervision from parents of student association.